SIGHAT IJAB KABUL TRANSAKSI JUAL BELI: PERSPEKTIF ULAMA KALIMANTAN SELATAN (Analisis Praktik Bermazhab di Kalimantan Selatan) - Saadah, Hj. Rusdiyah, Zainal Muttaqin, (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
Ulama(Islamic Scholars) who obligatetheconsentandagreement (shigat) in the form ofspeechgrantedbycertain wordssuch as"buying and selling" indicates that those ulamaare from Syafiiyyahschool of thought with qaulypattern.sect. Theulamawho require the obligationof shigatbut withno certain words as above, is saidtobe in the school of thought with manhajypattern. Theulamawho does not obligate the saying of (shigat) is not Syafiiyyahoriented,and is not tied toa particular school of thought. In the context ofshigat, these ulamaarguebased onscholarly opinionsstatingthat the transactionwithoutshigatis considered valid, and this transactionis calledBaial-muatah.